CardioLike-Net: An edge-end inter-patient arrhythmia classifier with quantization-aware-training for wearable ECG applications - Xu, Xinzi; Suo, Yanxing; Cai, Qiao; Zhang, Yunfang; Chen, Qinyu; Gao, Chang; Wang, Guoxing; Zhao, Yang (Biomedical signal processing and control, 2026)
Wearable electrocardiogram monitors equipped with edge-end classifier is a transformative tool for managing cardiovascular diseases. Whereas, electrocardiogram pattern variations have posed difficulties in obtaining robust accuracy among different individuals. To address this issue, this paper proposes a novel neural network architecture, resembling the diagnosis procedure of cardiologists while utilizing the robustness of artificial intelligent models. Also, this work introduces a quantization-aware-training algorithm that enables weight and activation quantization within recurrent neural network layers, which has traditionally been difficult due to their temporal dependencies and complex internal structure. Evaluated on a widely used public electrocardiogram dataset, it shows over 96.4% inter-patient classification accuracy across 43 subjects, which is superior to other state-of-the-arts. The quantized model maintains accuracy with only a 0.1% loss while reducing model precision to 4-bit integer weights and 6-bit integer activations. When deployed on a field-programmable gate array, the proposed classifier consumes 24 mW at a maximum clock frequency of 40MHz with a latency of 420ms. Compared to the full-precision counterpart, the hardware resource usage is significantly reduced, including reductions of 47.2% in look up tables, 45.5% in flip-flops, 78.9% in block memories, and 93.0% in digital signal processors. The source code is available at https://github.com/xinziXu/CardioLike-Net.git. •Architecture: This work introduces a CardioLike-Net architecture, inspired by the diagnostic process of cardiologists, reducing feature redundancy and the adverse impact of electrocardiogram signal variations.•Quantization: A novel quantization-aware-training algorithm is proposed to quantize the recurrent neural network layers to low-bit while maintain high accuracy.•Implementation: An edge-end arrhythmia classifier with high inter-patient accuracy and low hardware resources is achieved.